Design and investigate the manual sun tracking system - 'Imran, Ahmad Rosdi (2012)
According to market economy, the increasing worldwide demand for energy has continuously forces a rise on the price of fossil combustibles. In fact, the demand for energy is expected to grow faster than the finding out of new available fossil resources in the near future. The sun or solar energy had been identified as the most powerful energetic power source in our planet and it is expected that the sun will become the main electricity production source. The solar energy distribution is more depended on the position of the panel and the sun location. This project is about designing and analyzing the manual sun tracking system that can follow the sun movement. The objectives for this project are to design and analyze the single axis sun tracking system for flat plate solar collector. This project involves designing five main part of the manual sun tracking system which is frame, base, link, crank and pin. The analysis is done using SolidWorksSimulationXpress, ALGOR(FemPro) and Sam6.1. SolidWorksSimulationXpressis used to simulate and analyze the frame, base, link and crank part while ALGOR(FemPro) are used to simulate the designing part of pin. Sam6.2 is used to simulate and analyze the mechanism of the assembly design. All the designed part have safety factor more than one and are properly design and stable. However field test should be done to validate the final design and study the effect of the sun tracking system to solar collector.